Financial Performance of Loan and Guarantee Funds in Poland. How Business Elements Influence It? - Halina Waniak-Michalak; Jan Michalak; Edyta Gheribi (Journal of Accounting and Management Information Systems (JAMIS), 2018)
The main aim of the article is to evaluate performance of loan and guarantee funds in Poland. The system of SMEs support through loans and guarantees in Poland was created 24 years ago and it is ready for assessment. In many other countries similar institutions operate, however the question: How stable are the funds? "has not been asked yet. We analyze the elements of business models that influence the financial performance of researched organizations focusing on value proposition, channels, resources as well as some external factors (the region in which the fund operates.). To evaluate the financial performance of loan and guarantee funds we used data from financial statements for the year 2015 of 59 loan and guarantee funds (all funds that sent their financials for 2015 to the National registry in Poland). We observed that the level of the support provided by loan and guarantee funds in Poland is still relatively low. Most of researched funds are liquid but attain very low profitability. We found a significant positive impact of the width of value proposition, high quality of information channels, amount of resources and partnerships with financial institution on financial performance. We observed a positive effect of partnerships of the funds with financial institutions and high amount/ quality of resources on financial efficiency of funds. Finally, we noted also a negative influence of diminishing resources on financial stability (measured with the current ratio, but not with the default rate).
Keywords: G2; H2; O16; 650; small and medium enterprise; finance; loan funds; equity gap; guarantee funds; efficiency; support; system; business model